Fintech and financial inclusion : leveraging digital finance for economic empowerment and sustainable growth - Sharma, Vikas (Associate professor) (Routledge international studies in money and banking, 2025)
"Fintech and Financial Inclusion is a comprehensive edited volume exploring the transformative impact of financial technology on expanding access to financial services and fostering sustainable economic development. This collection brings together insights from leading scholars and practitioners across 20 chapters, offering a multifaceted examination of fintech innovations and financial inclusion globally. The book covers key topics such as the role of financial and digital literacy, fintech's impact on financial systems and economic growth, and case studies from countries like Ghana and India. It delves into technological aspects of fintech, including AI in banking and social media in financial education, while also addressing trends, challenges, and opportunities in fintech adoption. The volume doesn't shy away from ethical considerations and risks associated with fintech, exploring issues of security, privacy, and trust in digital finance. Gender equality in financial inclusion receives significant attention, with a focus on empowering women through financial access. Throughout, the book provides a balanced mix of theoretical frameworks, empirical studies, and practical insights, making it an invaluable resource for academics, policymakers, fintech entrepreneurs, and financial sector professionals. By bringing together various perspectives, this volume enhances our understanding of how technological innovations can create more inclusive and sustainable financial systems worldwide, addressing both the transformative potential of fintech and the challenges for responsible implementation in diverse economic contexts"--